Management of the planned change in teaching of public educational institutions (Encuentros, 2021)
The objective of the study was to analyze the management of the planned change in the teaching personnel of the educational institutions of basic secondary of Santa Marta, Magdalena, Colombia, theoretically, it was based on authors such as Gongalves (2020), Prieto y otros (2019), Garbanzo (2016), Vásquez (2007), Raffini (2008), among others. Methodologically, it is descriptive, with a non-experimental, transectional, field design. With a population of thirty teachers. Data collection with a questionnaire of twenty-one (21) items, simple selection with five response alternatives, validated and with a Cronbach’s alpha reliability of 0.700. The results indicated that it is necessary to recognize the signs that show the need for change, being necessary to design a vision that leads to a guiding coalition towards change. performance, and with it improve productivity, worker satisfaction and the achievement of objectives.
Keywords: Educational management, organizational change, change management, planned change, basic education.